EFFORTS TO IMPROVE STUDENT'S SELF CONFIDENCE USING COLLABORATIVE LEARNING MODEL - Nurhayati Nurhayati; Rosmaiyadi Rosmaiyadi; Buyung Buyung (STKIP Singkawang, 2018)
One way to improve students' self-confidence is to implement a collaborative learning model. Improving students' self-confidence using collaborative learning models can be done by conducting classroom action research. The subject of this class action research is the students of class X MIPA 4 SMA Negeri 2 Ngaglik, Sleman, Yogyakarta School Year 2015/2016 consisting of thirty two students. This study consists of two cycles. Technique Data collection used is test and non test. The instrument of this study is the test of student achievement and student confidence questionnaire. Data analysis techniques consisted of the conversion of qualitative data to quantitative and student mastery calculation. The average of student achievement before treatment is 40.3125 with the complete proportion of students is 3.125% and after treatment is 87.9167 with proportion of student which is complete is 100%. The average student self-confidence before treatment was 96.46875 with moderate category and after treatment was 109.2188 with high category. The results showed that collaborative learning model can improve student's self-confidence.